Effect of Surface Crosslinking on the Wear and Friction Behavior of Tea Polyphenol Stabilized Ultra-High Molecular Weight Polyethylene for Total Joint Replacements - Shah, Nouman Ali; Ahmad, Adnan; Gul, Rizwan M.; Kamran, M. Ali; Ishaq, M. Aaqib; Shakir, Namra; Xu, Jia-Zhuang; Li, Zhong-Ming; Sagbas, Binnur (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2025)
Highly crosslinked ultra-high molecular weight polyethylene (UHMWPE) with vitamin E (VE) as an antioxidant is widely used for joint implants. VE helps resist oxidation but raises concerns about reduced crosslink density and wear performance. This research hypothesized that tea polyphenols (tPPs), such as lipid-soluble epigallocatechin gallate (lsEGCG) and epigallocatechin gallate (EGCG), could prevent the usual decrease in crosslink density caused by VE, thereby enhancing wear performance. The antioxidants were blended with UHMWPE at 0.2 wt% and surface chemically crosslinked using di-cumyl peroxide. The surface properties, including crosslink density, roughness, coefficient of friction, and wear performance, were evaluated in detail. The results showed that lsEGCG and EGCG blended UHMWPE had significantly higher crosslink density compared to VE stabilized UHMWPE, which was 17% lower than virgin UHMWPE. The coefficient of friction increased after crosslinking and was higher in tPPs blended UHMWPE, indicating a highly crosslinked network structure. The wear resistance of surface crosslinked tPPs stabilized UHMWPE was significantly higher than VE-stabilized UHMWPE. Additionally, a substantial number of scratches, furrows, and flakes were observed on the surface of VE-stabilized UHMWPE compared to tPPs stabilized UHMWPE. It was concluded that tPPs are promising alternatives to VE for improving the performance and longevity of UHMWPE-based implants.
Keywords: Highly cross-linked UHMWPE; Vitamin E and Tea polyphenols; Wear performance; Surface crosslinking; Total joint replacement; TOTAL HIP-ARTHROPLASTY; VITAMIN-E; LINKED UHMWPE; KNEE ARTHROPLASTY; MICROSTRUCTURE; ANTIOXIDANT; MECHANISMS; OSTEOLYSIS; Materials Science